Morphological exploration and characterization of roselle (Hibiscus sabdariffa L.) populations from state of Guerrero, Mexico - Alarcón-Cruz Noé; Ariza Flores, Rafael; Barrios Ayala, Aristeo; Noriega Cantú David H.; Legaria Solano, Juan Porfirio (Revista Mexicana de Ciencias Agrícolas, 2018)
During 2007 to 2009 period this study was performed. Taking place at facilities of Universidad Autonoma Chapingo, the aim was to morphologically characterize 47 collections of roselle (Hibiscus sabdariffa L.) that represented populations from the state of Guerrero. In morphological characterization 50 variables were assessed, which were divided into 40 quantitative and 10 qualitative variables. 25 were selected from the quantitative ones and five with high importance from the qualitative. For morphological data characterization correlations, correspondence and grouping analysis were used. The quantitative morphological characters that most contributed to differentiation of roselle genotypes were: width at the base of leaf’s main lobule, average length of fruit, average fruit perimeter, leaf’s vertical length, leaf’s left lobule angle, flower’s chroma (C) and average leaf’s color quantified by colorimeter (L). The qualitative characters that best helped to define roselle groups were leaf’s visual color, earliness, stem’s apparent color, bracts color and lack or presence of glands, which substantially contributed to segregate the groups.